Peculiarities of self-governing students of a higher education institution of a sports profile - Бондар, Анастасія; Ждамірова, Юлія (Slobozhanskyi Herald of Science and Sport, 2018)
Anastasiia Bondar & Yuliya Zhdamirova Purpose: determine the features of student self-government higher education institution of a sports profile. Material & Methods: 120 students of the Kharkov State Academy of Physical Culture. The theoretical-methodological analysis, the analysis of normative legal documents, the system analysis, the survey (questioning) are held. Results: motivational number of students-athletes to participate in student self-government including needs: in prestige, self-improvement, recognition; achieving success and avoiding failures; show power over others; in communication, the establishment of emotional ties with others; participation in the cognitive process. The organizational structure of the bodies of student self-government of the Kharkov State Academy of Physical Culture includes the student parliament, the student council of the hostel, the student trade union committee and the student scientific society, which interact with each other and have their leaders. Conclusions: the main motivations for participation in student self-government are 67% of the students surveyed who consider the possibility of self-realization, through public work and its importance for the educational institution. The main body of student self-government is the Student Parliament, the election of the heads of the organization takes place by secret ballot during the general conference of students, and all other decisions are taken by open voting.